Wheat and Grain Sorghum in Four-Year Rotations - A. Schlegel; J. Holman; A. Burnett (Kansas Agricultural Experiment Station Research Reports, 2021)
In 1996, an effort began to quantify soil water storage, crop water use, and crop productivity on dryland systems in western Kansas. Research on 4-year crop rotations with wheat and grain sorghum was initiated at the Southwest Research-Extension Center near Tribune, KS. Rotations were wheat-wheat-sorghum-fallow (WWSF), wheat-sorghum-sorghum-fallow (WSSF), and continuous wheat (WW). Soil water at wheat planting averaged about 9 in. following sorghum, which is about 3 in. more than the average for the second wheat crop in a WWSF rotation. Soil water at sorghum planting was only about 1.5 in. less for the second sorghum crop compared with sorghum following wheat. Grain yields of sorghum in 2020 in all rotations were near the long-term average. For wheat, grain yields in 2020 were similar after fallow following sorghum, but much less after wheat. Grain yield of recrop wheat averaged about 75% of the yield of wheat following sorghum. Grain yield of continuous wheat averaged about 60% of the yield of wheat grown in a 4-year rotation following sorghum. Generally, wheat yields were similar following one or two sorghum crops; however, averaged across years, wheat yields were 2 bu/a greater following two sorghum crops than following one sorghum crop. Average sorghum yields were the same following one or two wheat crops. Yield of the second sorghum crop in a WSSF rotation averages ~65% of the yield of the first sorghum crop.
Keywords: no-till; continuous cropping; wheat; grain sorghum